1999
DOI: 10.1002/(sici)1521-3927(19990301)20:3<103::aid-marc103>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling polymerization of 4-methyltriphenylamine

Abstract: SUMMARY: 4-Methyltriphenylamine was oxidatively polymerized in chloroform (CL) or propylene carbonate (PC) in the presence of ferric chloride (FeCl 3 ) at 508C. Polymerization proceeded more rapidly and the molecular weight of the resulting polymer was higher in CL than in PC due to the higher oxidation potential of the solution. The linear structure was confirmed by 13 C NMR, and the resulting polymer exhibited high thermal stability and electrochemical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 10 publications
(14 reference statements)
0
44
0
Order By: Relevance
“…There were 15 intense resonances due to 1 methyl carbon and 14 aromatic carbons. Aromatic regions of13 C NMR and DEPT45 spectra and assignment of PDNTA are depicted in Figure 7. The DEPT45 spectrum shows that the signals at 148.41, 144.94, 135.64, 134.59, 130.33, and 130.20 ppm are the quaternary carbons.…”
mentioning
confidence: 99%
“…There were 15 intense resonances due to 1 methyl carbon and 14 aromatic carbons. Aromatic regions of13 C NMR and DEPT45 spectra and assignment of PDNTA are depicted in Figure 7. The DEPT45 spectrum shows that the signals at 148.41, 144.94, 135.64, 134.59, 130.33, and 130.20 ppm are the quaternary carbons.…”
mentioning
confidence: 99%
“…Especially, the polymeric TAA derivatives exhibit extensive application prospects due to the potential advantages such as possibility of extended -conjugation and excellent film-forming property. The common reactions for the synthesis of poly(triarylamine) (PTAA) where TAA units are linked together in the main chain are Ullman reaction [5], palladium or nickel catalyzed coupling reactions [6], and simple oxidative polymerization using ferric chloride as an oxidizing agent [7,8]. Recently, our group have.…”
Section: Introductionmentioning
confidence: 99%
“…The block copolymers containing triphenylamine and perylenediimide as side groups were also prepared [14,15]. Poly(triphenylamine)s (PTPAs) were firstly prepared by oxidative coupling polymerization of triphenylamine derivatives, and it was found that soluble poly(4-butyltriphenylamine) showed high hole mobility and high photoconductivity [38,39]. Recently, we have developed novel synthetic route for the preparation of PTPA utilizing palladium-catalyzed C-N coupling polymerization [40].…”
Section: Introductionmentioning
confidence: 99%